Emancipatory practices of nurses in primary health care: the home visit as an instrument of health needs assessment - Celia Maria Sivalli Campos; Bárbara Ribeiro Buffette Silva; Deisi Cristine Forlin; Carla Andréa Trapé; Iara de Oliveira Lopes
Objective Identify nurses' emancipatory practices in primary care, to contribute to the improvement of health care. Method A case study type social research of qualitative nature, in which nurses of a primary health care service unit in São Paulo were interviewed. Results The home visit was identified as a nursing practice possible to be expanded in order to identify social determinants of health, triggering emancipatory practices in the service. This expansion occurred because the design of health care labour intended by the service team changed its focus from the traditional object of health services, the disease. Conclusion First, it is advocated that social policies lead projects with the purpose of improving health needs. On the other hand, the daily labour needs to provide opportunities for reflection and discussion of healthcare projects, leading workers to propose labour-processes targeted to both the social determinants of health and people's illness.